2022
DOI: 10.3390/ph15030344
|View full text |Cite
|
Sign up to set email alerts
|

Two Lignan Glycosides from Albizia julibrissin Durazz. Noncompetitively Inhibit Serotonin Transporter

Abstract: Albizia julibrissin Durazz. is one of the most common herbs used for depression and anxiety treatment, but its molecular basis and mechanism of action as an antidepressant or anxiolytic drug are not understood. In this study, we separated and identified two lignan glycosides that inhibit serotonin transporter (SERT) noncompetitively by decreasing Vmax with little change in Km for its fluorescence substrate. In addition, treatment with lignan glycosides did not alter total and cell surface expression levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 65 publications
1
15
0
Order By: Relevance
“…Substrate 5-HT, which stabilizes the cytoplasmic-facing conformation of SERT in the presence of both Na + and Cl − (Forrest et al, 2008), significantly increased the reactivity of S277C, promoting its inactivation by MTSEA (Figures 3A,B, third image and second column from left, respectively), consistent with our previous observation that 5-HT induced conformational conversion from outward-facing to inward-facing (Huang et al, 2022). In contrast, fluoxetine, a SSRI, markedly decreased the reactivity of S277C, protecting it from MTSEA inactivation (Figures 3A,B, second image and second column from right, respectively).…”
Section: Influence Of (-)-Syringaresinol-4-o-β-dapiofuranosyl-(1→2)-β...supporting
confidence: 90%
See 4 more Smart Citations
“…Substrate 5-HT, which stabilizes the cytoplasmic-facing conformation of SERT in the presence of both Na + and Cl − (Forrest et al, 2008), significantly increased the reactivity of S277C, promoting its inactivation by MTSEA (Figures 3A,B, third image and second column from left, respectively), consistent with our previous observation that 5-HT induced conformational conversion from outward-facing to inward-facing (Huang et al, 2022). In contrast, fluoxetine, a SSRI, markedly decreased the reactivity of S277C, protecting it from MTSEA inactivation (Figures 3A,B, second image and second column from right, respectively).…”
Section: Influence Of (-)-Syringaresinol-4-o-β-dapiofuranosyl-(1→2)-β...supporting
confidence: 90%
“…Our previous study has demonstrated that SAG noncompetitively inhibited SERT activity ( Huang et al, 2022 ). To examine the possibility that SAG binds to the allosteric site, we conducted the molecular docking of SAG to hSERT, hDAT, and hNET on the hSERT structure and the hDAT and hNET models in an outward open conformation, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations